Urban Renewal as an Approach to Increasing the Housing Stock in Cities: Al-Malaz Neighborhood in Riyadh, a Case Study - Alzamil, وليد; Bin Suwailem, منار (Journal of King Abdulaziz University: Environmental Design Sciences, 2025)
This paper discusses the decline of residential neighborhoods and the resulting population migration and the lack of use of abandoned and old housing in urban areas, despite the availability of integrated infrastructure. these neighborhoods have become unutilized. The research aims to apply urban renewal methods as an approach to increasing the housing stock to increase the products and housing units that meet the needs of citizens. The study was applied to the Al-Malaz neighborhood in the city of Riyadh. The research followed a descriptive analytical approach based on reviewing a number of government reports and statistics. The research uses field survey tools of the case study model to analyze the residential uses in the Al-Malaz neighborhood that are abandoned by the original population and find out their condition, by assessing the current situation of the residential product in the Al-Malaz neighborhood. The research found that there is a housing stock in the Al-Malaz neighborhood in average condition, constituting 92%, which is the largest percentage, 2% in good condition, and 6% in poor condition, with different floors. It also found that there are 21 vacant plots of land in the neighborhood, which represents an opportunity in the urban filling process, filling empty gaps, and exploiting the land to increase the housing supply. The study also emphasized the application of urban renewal methods through partial development, rehabilitation, and complete removal of the current housing stock according to the urban condition, in order to provide a larger number of homes for affordable housing. Finally, the research paper recommends the need for entities to adopt the concept of urban renewal as an approach to increasing the housing stock.